MENTAL DERAILMENT AMONG TRIBAL WOMEN IN KERALA - Meera Bai M (ACADEMICIA: An International Multidisciplinary Research Journal, 2015)
Poverty, gender discrimination, use of alcohol , stress of modern life, conflicts and natural disasters are the major risk factors identified for mental illness nation- wide. But in the absence of an official mental health survey, there is little data on the number of people who suffer from this illness